PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN CUSTOMER RELATIONSHIP MARKETING TERHADAP KEPUASAN PASIEN RAWAT JALAN PADA RSUD DR MUHAMMAD ZEIN PAINAN KABUPATEN PESISIR SELATAN - Nanda Harry Mardika; Symponi Indra (JURNAL AKUNTANSI BARELANG, 2019)
The Purposes of this Research aim to determine the effect of the quality of products, service quality and Customer Relationship Marketing in partially and simultaneously to the Satisfaction of patients at In Hospital Outpatient DR. Muhammad Zein Painan South Coastal District. Metodhology of this research was used quantitative descriptive methods and multiple linear regression analysis wich used SPSS version 20.0. By using 100 samples, the result shows that quality of products, service quality and Customer Relationship Marketing partially and simultaneously have a positive and significant influencing to the In Hospital Outpatient DR. Muhammad Zein Painan South Coastal District. The regression equation for these three variables is Y = 12 469 + 0, 229 X1 + 0, 493X2. + 0, 260X3. The magnitude effect of three independent variables as together to the dependent variable is 47,9% and 52.1 % is influenced by other variables which are not examined in this study.